Anaemia following medical leech therapy for caudal superficial epigastric skin flap salvage in a Shorthaired Chihuahua. Issue 4 (27th September 2021) - Wang, Zhe; Upchurch, David A.
Abstract: A 6.5‐year‐old, 6.1 kg, spayed female Shorthaired Chihuahua was referred for surgical removal of a mast cell tumour regrowth on the right caudal thigh. In the right perineal region lateral to the base of the tail, there was a 4 × 5 cm soft tissue mass with focal alopecia in the centre. Complete excision of the mass was achieved with a caudal superficial epigastric skin flap for closure. At 5 days postoperatively, the distal 25% of the skin flap showed evidence of venous congestion. Medical leech therapy was performed, and the flap was salvaged successfully; however, the dog developed acute anaemia due to excessive blood loss and received a packed red blood cell transfusion. The dog recovered uneventfully after transfusion and the skin flap had healed completely at recheck (26 days postoperatively). To the authors' knowledge, this was the first report of anaemia requiring blood transfusion after leech therapy in dogs.